THE STRESS REFLECTED IN PETE DOCTER’S SOUL (2020) MOVIE - Yoga Ayudha Aqidho; Atinia Hidayah (CLLiENT (Culture, Literature, Linguistics, and English Teaching), 2021)
Stress is a familiar word in the modern era, it appears even in the movie without anyone is aware. This research discusses the stress phenomenon reflected in Pete Docter’s Soul (2020) movie. The objective of the research is to explain appraisal and coping, the two basic concepts of stress that appear in the Soul (2020) movie. The qualitative method is used in this to explore the stress phenomenon deeply. The research is conducted by applying stress, appraisal, and copping theory by Richard S. Lazarus and Susan Folkman as the based theory to examine the data research. As result, stress revealed on the character in Soul (2020) movie has two components which are appraisal and coping that have their function to increase and decrease stress. While most of the appraisal is increases stress of the characters, it apparently enhances the well-being of the characters or does not affect the character's stress level. Furthermore, coping appears to relieve stress the character gained from the event they have encounter.